Psychosocial determinants of oral health outcomes in young children - Kopycka-Kedzierawski, Dorota T.; Ragusa, Patricia G.; Feng, Changyong; Flint, Kim; Watson, Gene E.; Wong, Cynthia L.; Gill, Steven R.; Billings, Ronald J.; O’Connor, Thomas G. (Frontiers in Pediatrics, 2024)
Objective To examine the social determinants of early childhood caries (ECC), one of the greatest public health risks affecting children, and examine alternative pathways of influence. Methods A physically healthy, socio-demographically high-risk sample of initially caries-free children, aged 1–4 years, was prospectively studied for 2 years. At 6-month intervals, assessments were made of caries presence from a standard dental exam; oral microbiology was assayed from saliva samples; oral hygiene behaviors and psychological and psychosocial risk exposure were derived from interviews and questionnaires. Results 189 children were enrolled; ECC onset occurred in 48 children over the 2-year study period. A composite measure of psychosocial risk was significantly associated with ECC onset over the course of the study (1.57, 95% CI 1.12–2.20, p < .001) and significantly associated with multiple risks for ECC, including poor diet/feeding (.92; 95% CI. 22–1.61, p < .01), poor oral hygiene (.39; 95% CI .09–.68), p < .05), and higher concentrations Lactobacilli (.96; 95% CI .43–1.49, p < .001). Multivariable regression analyses provided indirect support for the hypothesis that psychosocial risk exposure predicts ECC onset via behavioral and oral hygiene pathways. Conclusions The study provides novel evidence that psychosocial factors influence many of the purported risks for ECC and strong evidence that there are social and psychological determinants of ECC onset.